Identificação da vitimização por stalking no Brasil - Abreu, Vanessa Akemi Odahara (Universidade Federal de São Carlos, 2019)
Stalking can be described as a form of interpersonal violence characterized by behaviors of persistent harassment with repetitive, intrusive and intimidating patterns directed toward a victim who feels troubled and intimidated by such conduct. The phenomenon, although approached by the media and newsreels, is still not criminalized in Brazil. In countries where it is criminalized, fear is often used as criteria to delimitate the division between criminality and the legal and social legitimacy of stalking. The main goal of this project was to replicate, in Brazilian territory, the research “Vitimação por stalking: Preditores do medo” (2012), which was carried out by Matos, Grangeia, Ferreira and Azevedo in Portugal. Seventy-eight men and 203 women aged 18 to 60 years participated in the survey, who responded to an online form that contained an adapted version of the Vitimação por stalking: Preditores do medo. Of the 281 participants, 115 (40.6%) reported stalking at some point in their lives. The results pointed to a greater victimization of women, as in the stalking literature, with men constituting the majority of the offenders of the phenomenon. It was also noted that women perceived victimization as more frightening than men, and felt more psychologically affected by the experience. On the other hand, they sought more help than men to solve the situation and, comparatively, felt more helped by others. The gender variable influenced most of the research findings, and points to a considerable difference in the perception of society and the victims themselves regarding victimization. This perception is based on historical and cultural elements of the construction of patriarchy, which instigate gender violence that is related to the main characteristics of stalking. Therefore, attention is paid to the need for future studies in the area in order to better understand the phenomenon and its various facets.
Stalking identification and victimization in Brazil
Keywords: Stalking; Assédio persistente; Medo; Vitimização; Persistent harassment; Fear; Victimization; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA